Лексичні інновації в музиці. - Гладкоскок, Леся Григорівна; Мурадханян, Ірина Саркісовна; Семен, Галина Ярославівна (Вчені записки Таврійського національного університету імені В. І. Вернадського., 2022)
Muradkhanian I. S., Hladkoskok L. H., Semen H. Ya. LEXICAL INNOVATIONS IN MUSIC The article is devoted to the issue of lexical innovations in the sphere of music. The material for the analysis was 72 units selected from English-Ukrainian Dictionary of Innovations in the Vocabulary of the English language at the beginning of the XXI-st century by Yu. A. Zatsnyi and A. V. Yankov (41 examples), Dictionary of New Words and Meanings by Z. S. Trofimova (21 examples) and Internet sources (10 examples). Lexical innovations in the sphere of music constitute a small part of new words, fixed in the academic dictionaries – only ≈ 2%, but the value of them lies in the reflecting the changes that occurred in the field of music during the recent time. The problem was tackled by O. Stepanova. L. S. Peretsman. J. M. Crotty, F. McAlpine, M. Daniels, but the development of new technologies, changes in the society need new nominations for different phenomena, music including. One of the ways of new words formation in the world of music is derivation, both prefixation and suffixation. Compound words are coined by means of two or more lexemes that constitute the terminological unity. Both two-member and three-member word combinations are observed. Some words are formed with the help of blending: ethnomusicology = ethnic + musicology. Among music innovations occur root/stem words. Fairly less such ways of new words coinage as the change of a letter in the word, conversion, the change of the second part in the known lexical unit, acronymy are observed. Ways of innovations wordbuilding are very rarely found in their pure form. Mostly there is a combination of different kinds for the coinage of new words. A vivid example of it may be words, the root of which is the element celeb-. Known words acquire new meanings. Special interest arises the phenomenon of transference of a lexical unit into another sphere and obtaining some new meaning by means of transference. Words that belong to music sphere are used in politics, job placement, work management, sociology and psychology. The dictionaries of innovations include, besides the words and word combinations, certain phraseological units and citations from the songs. The article regards only verbal music terms, graphical music terms (symbols, letters, numbers) were not found. The perspectives of the research are the usage of music terminology in the text of modern English sources
Keywords: музична термінологія; лексичні інновації; злиття; деривація; словотвір